Android Based Wedding Organizer Service Ordering Information System - Naihely, Stefanus Apriyanto; Kelen, Yoseph Pius Kurniawan; Syarifuddin, Risald (Politeknik Negeri Lhokseumawe, 2025)
Salon Michelle, as one of the wedding organizer service providers, is experiencing an increase in demand for wedding organizer services. The process of ordering wedding organizer services at Salon Michelle, which is still done manually, presents various challenges, such as the length of time it takes to make an order, difficulties in managing schedules, coordinating with clients, and the risk of communication errors with potential customers. Therefore, to make it easier for prospective brides and grooms to choose wedding packages available at Salon Michelle, an information system for wedding package providers is needed that provides complete information regarding the wedding packages offered by Salon Michelle vendors. By using this information system, it is hoped that customers can adjust their needs and desires to the availability of wedding facilities on offer, as well as see in detail the prices and facilities that can be obtained from Salon Michelle vendors, so that it will be very helpful in organizing wedding receptions.